Using pictures in teaching short story to non-proficient students / Najihah Talaha - Talaha, Najihah (2014)
The standardized literary texts that are used by all students in schools regardless of their different English language abilities can cause a burden to non-proficient students. There are still not many suitable techniques and approaches used by teachers to teach literature even though the Literature Component has been introduced more than a decade ago. Although there are not many studies done particularly on the effects of using pictures to teach literature, several researchers suggested that the presence of visuals does improve comprehension. However, there are still many teachers who prefer to use written texts over pictures because pictures bear the stigma of being entertaining only to children and not appropriate for serious academic works. Therefore, the main purpose of this study was to suggest a suitable and interesting teaching method that can be used by teachers to teach short stoiy to non-proficient students. It was carried out by investigating to what extent the presence of pictures help non-proficient students to understand short story. It also investigated the roles of pictures in learning the literature component, specifically short story, as well as examined students and teachers’ perceptions of using pictures in the teaching and learning process. Sixty Form 4 non-proficient students from one of the secondary schools in Kemaman, Terengganu participated in this study. The experimental group (n=30) was exposed to the research treatments; while, the control group (n=30) went through the learning without pictures. This study found that there is a significant difference between the non-proficient students learning by using pictures and those learning without pictures in understanding the short story. Besides, the participants were satisfied to be exposed to learning activities that incorporate the pictures in the teaching and learning process. Therefore, the stigma that pictures are entertaining only to children is not visible in this study. It is found that pictures have several roles in the nonproficient students’ teaching and learning short story, just like how pictures have improved students’ comprehension. This study also found that among the challenges in integrating pictures in the teaching and learning process is limited time available to prepare picture materials. In conclusion, it is suggested that pictures must be used to teach non-proficient students to learn short story due to many benefits they bring. It is also recommended that teachers should set up a group that shares the same interest to coordinate the production of picture materials.